2022
DOI: 10.1101/2022.09.30.22280573
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of mRNA-1273 against infection and COVID-19 hospitalization with SARS-CoV-2 Omicron subvariants: BA.1, BA.2, BA.2.12.1, BA.4, and BA.5

Abstract: Studies have reported reduced natural SARS-CoV-2 infection- and vaccine-induced neutralization against Omicron BA.4/BA.5 compared with earlier Omicron subvariants. We conducted a test-negative case-control study evaluating mRNA-1273 vaccine effectiveness (VE) against infection and hospitalization with Omicron subvariants. The study included 30,809 SARS-CoV-2 positive and 92,427 SARS-CoV-2 negative individuals aged ≥18 years tested during 1/1/2022-6/30/2022. While 3-dose VE against BA.1 infection was high and w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
22
1
Order By: Relevance
“…In contrast, a cohort study in Portugal found reduced protection against severe outcomes during BA.5 predominance (4). This was similar to U.S. findings, which indicated that 3-dose VE against hospitalization was lower during the BA.4/BA.5 period compared with the BA.1 period, although these VE estimates did not account for time after the last vaccine dose (5). Third, infection-induced immunity in the population substantially increased during and after the BA.1 period.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, a cohort study in Portugal found reduced protection against severe outcomes during BA.5 predominance (4). This was similar to U.S. findings, which indicated that 3-dose VE against hospitalization was lower during the BA.4/BA.5 period compared with the BA.1 period, although these VE estimates did not account for time after the last vaccine dose (5). Third, infection-induced immunity in the population substantially increased during and after the BA.1 period.…”
Section: Discussionsupporting
confidence: 81%
“…Second, increased immune evasion of BA.4/BA.5 lineages has been shown in neutralization assessments and may contribute to lower VE (10). However, the extent to which reduced neutralization in vitro correlates with reduced protection against severe disease is unknown; available studies have shown mixed results (2)(3)(4)(5). A study from South Africa showed no difference in VE of 3 monovalent mRNA vaccine doses against hospitalization during the BA.4/BA.5 period compared with the BA.1/BA.2 period at the same intervals from vaccination, which was corroborated by findings from the United Kingdom showing similar VE against BA.2-or BA.4/BA.5-related hospitalizations (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reassuringly, however, our findings are consistent with previous evidence that vaccination remains protective against severe disease associated with the BA.4/BA.5 lineages, at levels comparable to those reported for the BA.2 lineage. 5,[19][20][21] Within our large sample of 49,976 BA.2 cases and 59,556 BA.4/BA.5 cases, vaccination was not associated with statistically meaningful differences in estimates of protection against progression from an initial outpatient diagnosis to subsequent illness requiring ED presentation or either hospital or ICU admission. As our study is limited to infected cases who received clinical molecular testing, it is important to note our findings do not measure the effectiveness of prior infection or vaccination against infection with either lineage BA.4/BA.5 or BA.2 lineages.…”
Section: Discussionmentioning
confidence: 58%
“…23 A study among Kaiser Permanente members found that VE of third and fourth doses against BA.4/BA.5-related hospitalizations was lower compared to BA.1/BA.2-related hospitalizations, whereas another study among individuals admitted to IVY Network hospitals saw this difference for a third dose but not for 2 or 4 doses. 24,25 The IVY Network study reported 3-dose VE of 79% (95%CI, 74-84%) and 60% (95%CI, 12-81%), respectively, during the BA.1/BA.2-predominant versus BA.4/BA.5-predominant periods 7-120 days after vaccination. 25 Potential explanations for lower VE during the period of BA.4/BA.5-predominance compared to BA.1/BA.2-predominance include longer intervals between booster dose receipt and outcomes, increased incidence of undocumented infections, and increased BA.4/BA.5 immune evasion.…”
Section: Discussionmentioning
confidence: 99%